Human Factors in AR-Enabled Human-Robot Collaboration for Fabrication-Centric Architectural Design Process: A Co-design Workshop Approach. - Wei Win Loy; Anthony Franze; Jared Donovan; Müge Teixeira; Matt Adcock; Markus Rittenbruch (Interaction Design and Architecture(s))
The emergence of collaborative robotics presents an opportunity for architectural designers to safely engage in design and fabrication through human-robot collaboration (HRC). By leveraging the adaptability, creativity, and design judgement of designers with the strength, repeatability, and design precision of robotic assistance, HRC has the potential to create a unified design-fabrication workflow. Recent advancements in augmented reality (AR) technology further enhance these prospects by enabling users to superimpose context-sensitive, computer-generated information in the real world. AR technology also provides situational awareness, which proves beneficial in the context of HRC. The maturation of AR technologies offers new possibilities for developing HRC systems tailored to architectural design-fabrication needs. Recognizing the pivotal role of human factors in HRC development process, this paper aims to explore the architectural designers’ needs to develop an AR-enabled HRC system that better supports the fabrication-centric design process, such as exploratory collaborative assembly tasks. Key findings highlight the necessity for a unified design-fabrication workflow, a clearer allocation of tasks between designers and robotic arms, an intuitive user interface, a streamlined interaction process, a better understanding of robot intentions and movements, intuitive procedures for error avoidance and correction, and enhanced user safety in HRC scenarios.